STRATEGI KOMUNIKASI KPID JAWA BARAT GUNA MEMBENTUK SIARAN BERKUALITAS - Mahesa Muhamad Fauzia Rahmat (JURNAL PURNAMA BERAZAM, 2020)
Nowadays, television has become a need for most people from any social class at all ages. Then, it becomes difficult to control the audience due to the accessibility with such a wide range of the consumers of television. For example, the children may watch a television program that is not intended for their age. Some other violations of broadcasting happen too. It is because there is no direct monitoring of the audience. Meanwhile, the one which could be monitored and should be controlled is the television shows itself. This becomes the task of Komisi Penyiaran Indonesia (KPI) or Indonesian Broadcasting Commission. Therefore, this study discusses about how Komisi Penyiaran Indonesia Daerah (KPID) of West Java in communicating with the local TV stations in West Java in order to form a good quality TV programs. This study aims at investigating the communication between KPID of West Java and the local TV stations in producing a quality broadcasts. The method used in this research is qualitative method with a descriptive study approach. The data was collected through observation and interview.